2022
DOI: 10.3389/fpls.2022.873036
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Venation Architecture in Relation to Leaf Size Across Leaf Habits and Vein Types in Subtropical Woody Plants

Abstract: Leaves are enormously diverse in their size and venation architecture, both of which are core determinants of plant adaptation to environments. Leaf size is an important determinant of leaf function and ecological strategy, while leaf venation, the main structure for support and transport, determines the growth, development, and performance of a leaf. The scaling relationship between venation architecture and leaf size has been explored, but the relationship within a community and its potential variations amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For instance, a significant difference in stomatal density between evergreen and deciduous tree species was observed in a moist tropical forest in South Asia ( Rahman et al., 2022 ). In contrast, another study conducted within a subtropical forest community in China reported no discernible difference in minor vein density between evergreen and deciduous species ( Peng et al., 2022 ). Nevertheless, a limited number of studies have investigated the coordination between minor veins and stomatal densities in evergreen and deciduous tree species.…”
Section: Introductionmentioning
confidence: 93%
“…For instance, a significant difference in stomatal density between evergreen and deciduous tree species was observed in a moist tropical forest in South Asia ( Rahman et al., 2022 ). In contrast, another study conducted within a subtropical forest community in China reported no discernible difference in minor vein density between evergreen and deciduous species ( Peng et al., 2022 ). Nevertheless, a limited number of studies have investigated the coordination between minor veins and stomatal densities in evergreen and deciduous tree species.…”
Section: Introductionmentioning
confidence: 93%
“…The macroscopic traits of leaf architecture (e.g. vein topology, hierarchy) are usually studied using chemical clearing followed by leaf scanning [5][6][7], while mesophyll width and cell size are usually estimated from micrographs [1,7]. While both methods provide reliable information, they remain invasive and result in the loss of leaf material.…”
Section: Introductionmentioning
confidence: 99%
“…During the longterm evolution, plants have evolved a series of complicated mechanisms, including morphological, physiological, biochemical changes to combat against imbalance of water metabolism and oxidative damage induced by water stress. For instance, plants display remarkably diverse leaf shapes and sizes in nature , and there seems to be a tradeoff between the leaf support cost and photosynthetic returns (Ma et al, 2022;Peng et al, 2022). In addition, when exposed to water deficit, such as in arid and semiarid environment with poor resources, plants are usually with a lower leaf area because water losses and carbon gain processes are tightly coupled .…”
Section: Introductionmentioning
confidence: 99%